The Manasseh hill country survey. - Zertal, Adam. (Culture and History of the Ancient Near East, 2004)
The book presents the results of a complete detailed survey of the eastern region of Samaria, mainly the Middle Jordan Valley, within the territory of Israel/Palestine. It is Volume 5 of the Manasseh Hill Country Survey publications. This project, in progress since 1978, and covering 2500 sq. km, is a thorough, metre-by-metre mapping of the archaeological-historical area between the River Jordan and the Sharon Plain, and between Nahal 'Iron and the north-eastern point of the Dead Sea. This territory is one of the most important in the country from the Biblical and archaeological view; and the survey is a valuable tool for scholars of the Bible, archaeology, Near Eastern history and other aspects of the Holy Land. This volume describes the area of the Jordan Valley between Wadi Fasael in the north and Wadi 'Aujah in the south. It is a fully revised and updated version of the Hebrew publication of 2012.